2017
DOI: 10.1007/s10753-017-0543-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-24 Modulates Staphylococcus aureus-Induced Macrophage Polarization by Suppressing CHI3L1

Abstract: Macrophages play a crucial role in host innate anti-Staphylococcus aureus defense, which is tightly regulated by multiple factors, including microRNAs. A recent study showed that miR-24 plays an important role in macrophage polarization. Here, we investigated the biological function of miR-24 in S. aureus-stimulated macrophages. The results revealed that miR-24 expression was significantly decreased in both human and mouse macrophage cell lines with S. aureus stimulation in a time-dependent manner. Moreover, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 26 publications
1
35
1
2
Order By: Relevance
“…Other studies have reported that CHI3L1 contributes to polarization to M2 macrophage [48][49][50], but in our results, K284-6111-administrated Tg2576 mouse showed lower mRNA level of Tnf, Il1b, Il6, and Cd86. Moreover, overexpression of CHI3L1 increased the expression of markers of M1 microglia, Tnf, Il1b, Il6, and Cd86, and inhibited by K284-6111 treatment.…”
Section: Discussioncontrasting
confidence: 94%
“…Other studies have reported that CHI3L1 contributes to polarization to M2 macrophage [48][49][50], but in our results, K284-6111-administrated Tg2576 mouse showed lower mRNA level of Tnf, Il1b, Il6, and Cd86. Moreover, overexpression of CHI3L1 increased the expression of markers of M1 microglia, Tnf, Il1b, Il6, and Cd86, and inhibited by K284-6111 treatment.…”
Section: Discussioncontrasting
confidence: 94%
“…IRAK-M deficiency in turn leads to elevated miR-24 levels, sustaining the disruption of monocyte homeostasis and aggravating atherosclerosis. Another study recently confirmed the role of miR-24-Chi3l1 interactions in Staphylococcus aureus-stimulated macrophages (Jingjing et al, 2017). MiR-24 was found to decrease both M1 macrophage polarization and production of proinflammatory cytokines, and induce both M2 macrophage polarization and secretion of anti-inflammatory factors.…”
Section: Mirnas Endothelial Dysfunction and Vascular Inflammationmentioning
confidence: 68%
“…This miRNA also regulates cytokine production in macrophages through targeting Chi3l1 ( 68 ). According to Jingjing et al, miR-24 overexpression significantly decreases the production of M1 phenotype markers such as iNOS, IL-6, TNF-α, CD86, and CD80 but increases the production of M2 markers such as Arg1, CCL17, CCL22, CD163, and CD206 in stimulated macrophages ( 69 ). Moreover, miR-24 exerts anti-inflammatory action by inhibition the production of pro-inflammatory cytokines in LPS-stimulated macrophages ( 70 ), and secretion of inflammatory mediators including TNF-α, IL-6, and IL-12p40, in response to infection through modulation of various genes involved in pathogen recognition and downstream signaling ( 71 ).…”
Section: Mirnas and Inflammationmentioning
confidence: 99%